ASEAN POLICIES IN RESPONDING TO MIGRATION PHENOMENA AND PREVENTING TRANSNATIONAL CRIME - Ferdyan Samuel Karunia; Regita Cahyani Rahmat; Ajeep Akbar Qolby; Adira Khansa Ayu Herdian (Polteknik Imigrasi, 2023)
Migration and transnational crime are global phenomena that affect this study. The aims of this study are to identify and analyze the policies adopted by ASEAN in dealing with the phenomenon of migration and prevention of transnational crime which is a global problem. This policy has a significant impact on security and stability in the ASEAN region. Through evaluating the effectiveness of their implementation, this study also aims to evaluate the extent to which these policies have been successful in maintaining peace and security in the region. By extending this abstract, this research will investigate the strategy, legal framework, and concrete steps taken by ASEAN to address the challenges of transnational migration and crime. This analysis is expected to provide in-depth insight into the role and impact of ASEAN policies in dealing with this problem, as well as provide recommendations for future policy improvements.